Cervical Preparation for Hysteroscopy Using Dilapan-S Three Hours before Surgery: A Randomized Controlled Trial - Roya Shahriyaripour; Shahla Chaichian; Kobra Tahermanesh; Ladan Haghighi; Roya Derakhshan; Babak Sabet; Samaneh Rokhgireh (IMR Press, 2024)
Background: Hysteroscopy is a pragmatic diagnostic and operative method for the assessment of uterine pathologies. Cervical preparation is an important step for hysteroscopy, and it is recommended in order to reduce complications. The efficacy of Dilapan-S and Misoprostol as two means of cervical preparation were evaluated and compared in this study. Methods: This randomized clinical trial was conducted on women referred to Rasoul-e-Akram Hospital outpatient department. A total of 120 menopausal and non-menopausal patients with no history of vaginal delivery were included in this study. 400 micrograms of misoprostol and Dilapan-S were used for cervical ripening three hours before hysteroscopy. Cervical dilation was measured by the diameter of the largest dilator inserted without resistance prior to hysteroscopy. The time needed to achieve 9 mm dilatation was recorded. Complications of the procedure were evaluated and compared in both groups. Results: The size of the largest Hegar dilator without resistance in Dilapan-S and misoprostol groups were 7.6 ± 0.86 mm and 6.05 ± 1.04 mm, respectively (p < 0.0001). Preoperative complications including headache and nausea were significantly higher in misoprostol group (p = 0.013). Applying Dilapan-S for cervical ripening significantly reduced the time of cervical dilation (p < 0.0001). Conclusions: Short-term application of Dilapan-S before surgery, due to proper preparation of the cervix, increases the chance of successful hysteroscopy, without causing intolerance or major complications in patients or necessitating a longer preoperative hospital. Clinical Trial Registration: the study was registered at https://en.irct.ir/ (registration number IRCT20191123045476N2).